Assessing the quality of angiographic display of brain blood vessels aneurysms compared to intraoperative state - Nikolić, Igor Miroslav; Tasić, Goran M; Jovanović, Vladimir T; Repac, Nikola R; Janićijević, Aleksandar M; Šćepanović, Vuk D; Nestorović, Branislav D (Vojnosanitetski pregled, 2017)
Background/Aim. Aneurysms in brain blood vessels are expanding bags composed of a neck, body and fundus. Clear visibility of the neck, the position of the aneurysm and surrounding structures are necessary for a proper choice of methods for excluding the aneurysm from the circulation. The aim of this study was to evaluate the reliability of spatial reconstruction of blood vessels of the brain based on the original software for 3D reconstruction of the equipment manufacturer and a personal computer model developed earlier in the Clinic for Neurosurgery, Clinical Center of Serbia, Belgrade, compared to intraoperative identification of these aneurysms. Methods. This study included 137 patients of both sexes. The presence of an aneurysm was verified by angiographic methods [computed tomographic angiography (CTA), multislice computed tomography angiography (MSCTA), magnetic resonance imaging angiography (MRA), or digital subtraction angiography (DSA)]. Results. The quality score (0 to 5) for CTA was 3.180 ± 0.961, MSCTA 4.062 ± 0.928, and for DSA 4.588 ± 0.758 (p < 0.01). The results of this study favorite conventional angiography as the gold standard for diagnostic of intracranial aneurysms.  Conclusion. The results of this study are consistent with current publications review and clearly recognize the advantages and disadvantages of diagnostic neuroradiological procedures, with DSA of brain blood vessels as a binding preoperative diagnostic procedure in cases in who it is not possible to clearly visualize the supporting blood vessel and neck of the aneurysm by using the findings of CTA, MRA and MSCTA.
Keywords: intracranial aneurysm; diagnosis; angiography; tomography; x-ray computed; magnetic resonance angiography; digital subtraction